If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5w + -10 = 3w + 6 Reorder the terms: -10 + -5w = 3w + 6 Reorder the terms: -10 + -5w = 6 + 3w Solving -10 + -5w = 6 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -10 + -5w + -3w = 6 + 3w + -3w Combine like terms: -5w + -3w = -8w -10 + -8w = 6 + 3w + -3w Combine like terms: 3w + -3w = 0 -10 + -8w = 6 + 0 -10 + -8w = 6 Add '10' to each side of the equation. -10 + 10 + -8w = 6 + 10 Combine like terms: -10 + 10 = 0 0 + -8w = 6 + 10 -8w = 6 + 10 Combine like terms: 6 + 10 = 16 -8w = 16 Divide each side by '-8'. w = -2 Simplifying w = -2
| 8x=100+3x | | 5x+35=2(x+8) | | 2r-6=3r | | S=187+0.225S | | 10-2z=-7z | | -f+3=-4f | | 7*3x=6x+9 | | x+1/3+x-2/6=x+6/12 | | -6j-8=-8j | | 1/4d+3/4=6 | | x+6/3+x-2/6=2x-3/12 | | 27=2-5(9-x) | | 3(t+1)=9 | | 1/2h-16=5/8h | | 8h+(-15h)+(-5)=(-19) | | 9+2x=15-3x | | 7(9+2x)=15-3x | | 4(c+2)=16 | | 4x/(x+2)=2 | | -(x)-6/2=15 | | 2j-3j+19=2 | | -12+n=1 | | x+9=5(2x+8) | | 80.75/z5 | | 7(9+-2x)=-33-7x | | x^2-7=4x-11 | | 1/9x^2-1=-3/4 | | 7(9+-2x)=3(5x-2) | | 4x+(4-x)-5=2x+3 | | 2(24-y)+2y=48 | | z=11+3(x+y)findx | | 7(9+-2x)=9(5x-2) |